LONG TERM NEUROLOGIC AND PSYCHIATRIC STUDIES OF SEQUELAE - Finley, Knox H. (1953)
For fuller understanding of the nature of infectious encephalitis, continuing study must be made of patients with regard to possible neurological sequelae or aberrations in behavior. The large outbreak of encephalitis in California in 1952 having offered opportunity for follow-up observation of a large series of patients, many of them children who had convulsions during the acute phase of the disease, pilot studies already have been started and funds are being sought for extending the scope of the investigation over a period of years. In early observations of patients included in the pilot study, changes in emotional and behavior patterns were noted in some instances. Thus far, with the exception of two infants who had recurrence of convulsions, patients who recovered apparently free of residual effects have remained so. Further neurological and psychiatric investigation should be carried out.